PERLINDUNGAN ANAK BERBASIS ORGANISASI LOKAL (Community-Based Child Protection) - Suradi Suradi (Sosio Informa, 2005)
Child protection is the responsibility of government and society as a whole. Their commitments to protect the rights of children might be coherent wit the transformation of social development approach that more paying attention to the role of local community and society. Regarding this approach, all potentials and resources available in the community and such as local institution need to be empowered and mobilized in order to make their con tribution more realistic for social welfare development, especially for child protection.